2017
DOI: 10.4103/jomfp.jomfp_71_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of odontogenic keratocyst and orthokeratinized odontogenic cyst using Ki67 and α smooth muscle actin

Abstract: Aim:This study aimed to demonstrate and evaluate the expression of stromal myofibroblasts (MFs) and epithelial cell proliferation using α-smooth muscle actin (α-SMA) and Ki67 markers, respectively, in odontogenic keratocyst (OKC) and orthokeratinized odontogenic cyst (OOC) to correlate their aggressive behavior.Materials and Methods:Twenty cases of OKC and twenty cases of OOC were stained with α-SMA and Ki67 markers for demonstration of stromal MFs and epithelial cell proliferation, respectively, and ten cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Thereby controlling lesion growth and vascular support through angiogenesis ( 10 , 16 ). Unfortunately, few studies on the presence of MF in odontogenic cysts are available ( 2 , 5 , 10 , 18 - 23 ) and only four address inflammatory odontogenic lesions ( 16 - 17 , 24 - 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby controlling lesion growth and vascular support through angiogenesis ( 10 , 16 ). Unfortunately, few studies on the presence of MF in odontogenic cysts are available ( 2 , 5 , 10 , 18 - 23 ) and only four address inflammatory odontogenic lesions ( 16 - 17 , 24 - 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…MFs are differentiated broblasts that express α-SMA and have intermediate characteristics between conventional broblasts and smooth muscle cells [30] being able to remodel and degrade the extracellular matrix by secreting matrix metalloproteinases, driving the invasive growth of lesions odontogenic cyst [31]. The few studies that investigated the presence of MFs in odontogenic lesions suggest that the increase in the number of these cells contributes to the progression of the lesion and more aggressive biological behavior [13,17,21,24,25,32,33]. Anusai et al [10] reported that epithelial and stromal cell interactions are fundamental in controlling the growth and clinical behavior of odontogenic cystic lesions and that MFs are seen in greater numbers in OKC than in DC.…”
Section: Discussionmentioning
confidence: 99%
“…3 While the latter is an aggressive lesion that tends to cause massive areas of destruction by proliferating in between the marrow spaces in an anteroposterior direction, the former is a relatively docile one. 5 The present case report describes an unusual case of extensive OOC that involved the majority of the angle and ramus of the mandible.…”
Section: Introductionmentioning
confidence: 86%